REMINDER EFFECT AND ANCHORING-ADJUSTMENT IN EARNINGS ANNOUNCEMENT: IMPLEMENTATION OF PRIORPERIOD BENCHMARK DISCLOSURE STRATEGY - Sri Wahyuni; Jogiyanto HM (Journal of Indonesian Economy and Business (JIEB), 2012)
The purpose of this study is to provide empirical support regarding the reminder effects and anchoring-adjustment in earnings announcements. This study is important to explainthe cognitive mechanism in processing the information that the consequences can affect the judgments of investors in evaluating company performance. The research of behavioralaccounting often focuses on the consideration in the framework of investment decision making mechanism based on a systematic and accurate. Prior researches have described strategic disclosure of prior-period benchmark in earnings announcement that focuses on the transitory gain or loss, which, in turn, influences investor’s judgments (Schrand & Walther 2000; Krische 2005). Using strategic reference-point theory from psychology and Hogarth & Einhorn’s (1992) belief-adjustment theory, this paper extends such research by investigating how investors behave differently to reminder effect and anchoringadjustment. The experimental results suggest that reminder effects and anchoring of information can influences investor’s judgments in evaluating of company performance.Keywords: reminder effect, anchoring-adjustment, cognitive mechanism, strategic reference-point theory, belief- adjustment theory